The association between blood selenium and metabolic syndrome in adults: a systematic review and dose–response meta-analysis of epidemiologic studies - Hajhashemy, Zahra; Foshati, Sahar; Bagherniya, Mohammad; Askari, Gholamreza (Frontiers in Nutrition, 2025)
Background and aim Although the relationship between selenium and metabolic syndrome (MetS) was previously investigated, the findings were inconsistent. Therefore, we performed a systematic review and dose–response meta-analysis to summarize the association between blood selenium and MetS in adults. Methods A comprehensive search was conducted in Medline (PubMed), ISI Web of Science, Scopus, and motor engineering of Google Scholar up to October 1st, 2024. Observational studies which reported the risk of MetS in relation to blood selenium in adults were included. The protocol of the current analysis was registered at PROSPERO as CRD42024486035. Results Overall, 16,779 participants and 6,471 cases with MetS from 5 cross-sectional and 7 case–control studies were included in the current systematic review and meta-analysis. The findings showed that participants with the highest blood values of selenium (mean: 268.5 μg/L) in comparison to those with the lowest values (mean: 75.27 μg/L) had 40% higher risk of MetS. Nevertheless, this association was not significant (95%CI: 0.99–1.97). Due to a significant between-study heterogeneity (I2 = 90.4%, p < 0.001), subgroup analysis was conducted based on potential confounders. However, this association was only significant in a few subgroups with low number effect sizes. Linear dose–response analysis illustrated each 50 μg/L increment in circulating selenium was related to 7% higher risk of MetS (RR: 1.07, 95%CI: 0.99, 1.15) However, this association was not statistically significant. Additionally, non-linear dose–response analysis indicated a U-shaped association between blood selenium and risk of MetS with the lowest risk at 160 ug/L of blood selenium (p < 0.001). Conclusion There is a U-shaped relationship between blood selenium levels risk of MetS. However, more longitudinal studies are needed to verify the causality of findings and clarify the underlying mechanisms.